Exploring Nurse-Patient Communication Strategies - Ali Fakhr-Movahedi; Reza Negarandeh; Mahvash Salsali (Tehran University of Medical Sciences, 2013)
Background & Aim: Nurses are informed from patients needs using effective mutual communications. This study aimed to explore the communication strategies between nurses and patient. Methods & Materials: This study had a qualitative approach with the content analysis method. Participants included 23 nurses, patients and their families in medical and surgical wards of Imam Khomeini hospital of Tehran University of Medical Sciences. Data were collected using interviews and observations. The first and second interviews were conducted unstructured. The semi-structured interviews were then conducted according to the derived concepts from the first and second interviews. We used observation in order to gain a deeper understanding and verifying data from interviews. The observations focused on the interactions between nurses and patients during mutual communications. Results: A final theme was emerged through the data analysis: adaptation of nurses&apos attitudes and performances. This theme derived from three main categories: caring according to acute needs of patients, creating a professional realm, and participation. The caring according to acute needs of patients included subcategories such as identifying patients&apos acute needs and nurses&apos communication behavior. Creating the professional realm implicated on the clarifying roles and maintaining of privacy communication. Participation was defined as the audience and content. Conclusion: The findings showed that nurses, in response to the underlying conditions of nursing care, assimilate their attitudes and performances to be able to meet their professional needs and their patients&apos needs. In fact, the main character of nurse-patient communication is nurses&apos active role and patients&apos passive role.